استراتيجيات تعليم اللغة العربية لدى المعلم المتفؤق في المدرسة الثانوية الوطنية الدينية "معهد حميدي كاجنج أغموزجا" - Noor Muhammad Othman
The Ministry of Education Malaysia was outlined several objectives for Arabic language teaching in secondary schools including mastering new vocabulary that not less than 800 words and its usability in speaking, listening, reading and writing by referring to appropriate Arabic dictionaries to improve vocabulary mastery. This study will aim at identifying strategies of Arabic language vocabulary teaching and sentences applied by excellent teachers through collection, acquisition and application strategies. The participant of this study is a person with broad experiences in Arabic language teaching and as well as an excellent teachers at Sekolah Menengah Kebangsaan Agama (SMKA) Maahad Hamidiah Kajang, Selangor. Qualitative approach was utilized in this study by conducting interviews as the research instrument. The data from interviews will be transcribed, compiled and analyzed using the themed coding using ATLAS.ti 7 based on the checklist of language teaching strategies adapted from Ibn Khaldun. The findings show that excellent teachers as respondents of the study have used all the strategies for collecting, acquisiting and applying mufrodat with Arabic sentences in the process of teaching Arabic language in schools. The findings also succeeded in collecting teaching strategies performed by excellent teachers in accordance with the objectives of the study which have been outlined, as well as suggesting methods of collection, acquisition and application should be used in the process of teaching in secondary schools to enhance Arabic language proficiency in secondary schools.